OCCUPATIONAL HEALTH AND SAFETY TRAINING - A SNAPSHOT OF EMPLOYEES' LEVEL OF KNOWLEDGE - Galya Stankova; Nevena Tzacheva; Lidiya Hristova (Peytchinski Publishing, 2021)
Introduction: The EU strategy "Europe 2020" sets up the instruments and targets for better educational levels and training as social dialogue, awareness-levels raising, law enforcement in the field of EU and national legislation. There are efficient resource interactions with other policy areas such as public health and education. EU funds, such as the European Social Fund (ESF) and the European Program for Employment and Social Innovation (EaSI), will support the application of rules relating to health and safety at work. Purpose of this study is analysis and evaluation of the employees, knowledge about health and safety at the workplace and how effective were the conducted OHS training. Tasks: Defining the level of awareness of workers for possibilities of health damage at work. Measuring the level of OSH training support for the implementation of preventive approaches to health protection in the workflow. Studying the preliminary psychological attitude towards OHS training both for employers and employees. Method: Survey through a questionnaire held among workers and employees in several branches of the private sector. Results: The study provides summarized information on several subjects: workers' knowledge about dangerous hazards in their own working environment; adherence of the safety at work rules; proper use of personal protective equipment and specific work protective equipment; types of training, outreach and education the employees have undergone; levels of basic knowledge of the law and regulations related to OHS; most common methods of OHS training and education and their interpretation for safety and health at work. Conclusions: Most workers are well aware of the health risks at their workplaces. All of them have passed at least one educational course related to OHS. More than 2/3 of the respondents have participated in several types of training. Workers have a basic knowledge of Bulgarian employment law, but it's incomplete and can be extended to a better degree. The most common reason for participating in Health and Safety at work training is obligatory both by law or higher management of the company. There is a high need to supplement the OHS legislation.